PEMETAAN PERILAKU OPPORTUNISTIK TERHADAP PROSPEK PERUSAHAAN MENDATANG MELALUI AKTIVITAS MANIPULASI - Siladjaja, Muljanto; Markonah (Indonesian Journal of Accounting and Governance, 2019)
This research have tested out the influence of opportunistics’s behaviour on the fluctuation of marketprice by using the manipulation activity later this research provide the mapping between investor’sdecision with accruals quality in financial reporting. Because of the usefullness information financialreporting, so that the investor can done the predicting the future prospect by estimating the growthrate, so it give the feedback to management. The dividend policy can be used s as the communicationprocess, management have proclivity to diseminate that the prospect had been better in the future. Theprevious research had tested out the using of accruals had been the negative perspective on investor’sview, so the research have developed out the estimation of discretionary accruals quality as an criticalmeasurement of reducing the opportunistic behaviour. This research used the statistics model bydeveloping the the multiple regresion by developing out the new indicators for the estimated price,that based on earnings and equity as independent variables. This research have the causal approachby using the purposive sampling on the manufacturing industry by using the real based manipulationactivity, so the manipulation activity had been treated as a proxy for grouping the patern ofopportunistics behaviour. By using future market value based on earning and equity, the investor haveenough capability in detecting the earning management, the investor have calculated the net marketvalue in predicting the company’s prospect in future. In this research have developed out the accrualsquality literature by mapping the feedback of interaction in decision tree model with Teorema Bayes.The positive perception of dividend policy show out the investor involvement in formulating cooperateoperational policy. The investor’s positive perception can be formed when they found “the good” newsby detecting out the negative manipulation and high accruals quality. It has paved the investor out theway in controlling and monitoring the company’s performance for the better prospect one.